Karonda (Carissa spp.): An Underutilized Minor Fruit Crop with Therapeutic and Medicinal Use - Debasish Panda; Satyajit Panda; Kalipada Pramanik; Sananda Mondal (International Journal of Economic Plants)
Karonda (Carissa spp.), a minor fruit crop is a source of ayurvedic and unani medicine and widely used in India as a medicinal plants by tribals. Different parts of this plant contain various chemical constitutents i.e. carissol, carissic acid, ascorbic acid, lupeol, β-sitosterol, glucose, galactose, serine, glutamine, alinine, valine, phenylalanine and glycine etc. This plant is commonly utilized for remedy of several diseases like biliousness, anemia and also used as aphrodisiac for women, antiparasitic, antifungal, antimicrobial, topical wound treatment (juice) and skin remedy. This paper reviews the literature supporting evidence for the medicinal and therapeutic uses of fruit, leaves, root and shoot of karonda along with its ethno-botanical relevance.